Pembatalan Surat Keputusan Bupati Oleh Penjabat Sementara Bupati - Rumadan, Muhamad Rizki; Nirahua, Salmon Eliazer Marthen; Saija, Vica Jillyan Edsti (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2024)
The Validity of the Regent's Decree which was annulled by the Acting Regent, which of course is motivated by regulations and/or laws, especially law Number 30 of 2014 concerning Government Administration, which in scope also regulates the requirements for the validity of decisions which contain the elements the authority of administrative officials or state administration officials of reviewed in terms of authority. Procedures and also the subtance of the objeckt of the decisions, as well as looking at the legal consequences of canceling decisions made by the acting Regent. This writing discusses two issues, namely: 1). Can the acting regent be able to cancel the Regent's Decree. 2). What are the legal consequences of the cancellation of the Regent's Decree by the Acting Regent.